ICOLLT 4.0 2024 WORKSHOPS: UNLEASHING ENDLESS KNOWLEDGE AND DISCOVERY GALORE - Azwin Arif, Abdul Rahim; Nor Yazi, Khamis; Wan Jumani, Fauzi (Pusat Bahasa Moden (PBM), 2024)
21 May 2024 – The second day of the Fourth International Conference on Language Learning and Teaching (ICoLLT) 2024 was no less uplifting with the demonstration and presentations from industry experts, and academics.